Implementation of Human Rights Values in Historical Learning in Educations - Ruslan, Ahmad; Syukur, Abdul; Kurniawati, Kurniawati (Journal of Education Reseach and Evaluation, 2020)
Human rights abuses are the center of every country in the world, as they are the result of their dominance over the weak, or other things like ignorance, lack of law enforcement, etc. And so it is in the world of education, which ought to be a center of understanding and awareness of human rights, through history study. But rather often, human rights abuses come from academic environments such as schools and colleges. The study aims to analyze the implementation of human rights values in history study. The study uses a qualitative method with a library research approach, whereas the data-collecting technique is a document or documentary study instrument. These findings suggest that the study of history has affected the behavior of students that reflect the virtues of human consciousness. Human rights values such as equality and the ban of discrimination (nondiscrimination) are reflected in students after the historical learning process is done, it can be seen both inside and outside the equation. Thus history study alone has significant effects on students, such as mutual respect of opinion, upholding the values of tolerance, cooperation and so forth. The conclusion of the article is that the effectiveness of learning needs to be optimized so that the human rights reflected in every historical event are capable of being thoroughly analyzed and understood by learners, which are then a provision for students to live national and national.